Eye movement tics. Issue 11 (November 1992) - Shawkat, F; Harris, C M; Jacobs, M; Taylor, D; Brett, E M
Abstract : An 8-year-old girl presented with opsoclonus-like eye movement and an 18 month history of intermittent facial tics. Investigations were all normal. Electro-oculography showed the eye movements to be of variable amplitude (10-40 degrees), with no intersaccadic interval, and with a frequency of 3-4 Hz. Saccades, smooth pursuit, optokinetic, and vestibular reflexes were all normal. These abnormal eye movements eventually disappeared. It is thought that they were a form of ocular tics.